POTENTIAL OF LITSEA GARCIAE METHANOLIC BARK CRUDE EXTRACT IN TREATING OKADAIC ACID-INDUCED ALZHEIMER'S-LIKE MODEL IN ZEBRAFISH - Siti Zaleha, Raduan; Qamar Uddin, Ahmed; MUHAMAD RUSDI, AHMAD RUSMILI; Awis Sukarne, Mohmad Sabere; Muhammad Salahuddin, Haris; Mohmad Farooq, Shaikh; WAN MOHD AZIZI, WAN SULAIMAN; Muhammad Hamdi, Mahmood (2025)
Introduction: Alzheimer's disease (AD) is a debilitating neurodegenerative disorder characterized by cognitive decline, memory impairment, and behavioural disturbances. Objectives: To evaluate the effects of methanolic Litsea garciae (LG) bark crude extract on anxiety, locomotion, learning, and memory, as well as its impact on AD-associated oxidative stress biomarkers and related molecular pathways Methods: AD-like behavior was induced in zebrafish via intraperitoneal administration of okadaic acid (OKA) twice a week. The zebrafish were immersed in LG-treated water for 21 days. Behavioral assessments, including the novel tank test for anxiety-locomotion and the T-maze for learning-memory, were performed, with data collected on days 7, 14, and 21. Brain tissues were harvested for immunoblot analysis and oxidative stress biomarker evaluation. Results: Behavioral assessments revealed that methanolic LG bark extract significantly (p<0.05) reduced anxiety and enhanced locomotor activity, memory, and learning in a zebrafish model of AD compared to the control. Immunoblot analysis demonstrated that LG extract significantly (p<0.05) reduced the expression of active phospho-GSK3β (Tyr216) at a minimum concentration of 50 mg/l and phospho-Tau (Ser9) at 25 mg/l. Furthermore, LG extract significantly (p < 0.05) alleviated oxidative stress, as indicated by reductions in lipid peroxidation (LPO) at 25 mg/l and increases in superoxide dismutase (SOD) activity at 50 mg/l. Conclusion: This study underscores the potential of the LG bark crude methanolic extract in mitigating oxidative stress and inhibiting the activation of GSK3β, leading to improved cognition potentially due to reduced Tau phosphorylation.